A comparative study of burst failure models for assessing remaining strength of corroded pipelines - Zhu, Xian-Kui (Journal of Pipeline Science and Engineering, 2021)
•A comprehensive review of corrosion assessment models was provided for corroded pipelines.•The existing corrosion models were categorized into three generations in terms of their reference stress.•The first generation of corrosion models was empirically developed based on the flow stress during the 1950–1970s.•The second generation of corrosion models was numerically developed based on the ultimate tensile stress (UTS) during the 1990–2000s.•The third generation of corrosion models remains in developing based on the UTS and strain hardening rate since the 2000s.•A new third-generation model is proposed and validated by full-scale experimental data.•Recent progress and major technical challenges were discussed for improving the current corrosion assessment models. This paper performs a comparative study of remaining strength assessment models for corroded pipelines. A brief review of burst prediction models is first given for defect-free pipes, including strength solutions and flow solutions of burst pressure and experimental validations. Followed is a review of corrosion assessment models that are categorized into three generations in terms of the reference stress used in each model. Those corrosion models are then evaluated in comparison to full-scale burst data, with a focus on validating the newly proposed third-generation models. Next, recent progresses are discussed, including the PRCI corrosion assessment projects, constraint effect, bulging factor and defect width effect. Major technical challenges facing the corrosion model improvement are finally discussed with regards to full-scale tests, numerical modeling, material failure criteria, and real corrosion defects.